DIAGNOSIS OF NITROGEN AND NICKEL REQUIREMENTS FOR COTTON PLANTS USING A PORTABLE CHLOROPHYLL METER - Barcelos, J. P. Q.; Furlani Junior, E.; Reis, H. P. G.; Putti, F. F.; dos Reis, A. R. (Revista Brasileira de Engenharia de Biossistemas, 2016)
Nitrogen is the most required nutrient by cotton plants, and its storage form in plants involves ureides and arginine, which makes nickel (component metalloenzyme urease) essential for metabolism and efficiency of nitrogen utilization by cotton plants. This study aimed to evaluate the response of cotton cv. FMT-701 due to combination of nitrogen and nickel application. The experiment was carried out under greenhouse conditions using pots containing 5 dm-3 of Oxisoil distrofic. The experiment was conducted on an entirely randomized design and a factorial scheme 4 x 4; where 4 levels of nitrogen (0, 40, 80, and 120 kg ha-1) and 4 levels of nickel (0, 50, 150 and 300 g ha-1), totaling 16 treatments with 3 replications. The chlorophyll was monitored at 1, 2, 8, 16, 24, 32, 40 and 48 days after application (DAA) of urea. Levels of nickel show no effect on chlorophyll index. On the other hand, the application of urea showed a significant increase on chlorophyll index especially during 40 and 48 DAA. The same effect was not found for nickel application. The range between 45 and 90 kg ha-1 of nitrogen resulted in higher chlorophyll index. Thus, our results suggest that it is not necessary to apply levels of nitrogen above 60 kg ha-1, which means a great economy on nitrogen fertilizer application to cotton plants. The chlorophyll index was highly positively correlated to leaf nitrogen concentration but no relationship was found to foliar nickel concentration. The chlorophyll index increased in cotton leaves during development stage in all treatments. The use of portable chlorophyll meter to evaluate the nitrogen status requirement is a promising tool to detect possible nitrogen deficiency in cotton plants.